Synthesis and curing of amino‐containing benzoxazine as a novel hardener for diglycidyl ether of bisphenol‐A. (20th February 2019) - Ren, Shitong; Zhang, Shaoyue; Zhao, Weibo; Wang, Wei; Miao, Xiangyan; Song, Wanqiang
Abstract : Benzoxazines containing various additional functional groups have been extensively reported to improve the properties of polybenzoxazines. In this work, a novel amino‐containing benzoxazine (PDETDA‐NH2 ) was conveniently synthesized from diethyltoluenediamine (DETDA), 2‐hydroxybenzaldehyde, and paraformaldehyde and was used as a hardener for diglycidyl ether of bisphenol‐A (DGEBA). The curing behaviors of PDETDA‐NH2 and PDETDA‐NH2 /DGEBA systems were studied by DSC, FT‐IR, and 1 H NMR. When curing, PDETDA‐NH2 was firstly polymerized to N, O ‐acetal‐type polymer and then rearranged to Mannich‐type polymer at elevated temperature, while the addition reaction between amino and benzoxazine was discouraged because of the steric hindrance of alkyl substituents. During PDETDA‐NH2 /DGEBA curing, it was found that the reactions happened in the order of addition polymerization of amino and epoxide, ring‐opening polymerization of benzoxazine, etherification between phenolic hydroxyl of the polymerized benzoxazine, and epoxide. Compared with DETDA cured DGEBA, PDETDA‐NH2 cured DGEBA showed higher modulus, higher char yield, and much lower water uptake.